"Unir pontos num novo desenho": um estudo sobre a trilogia luso-brasileira de Alexandra Lucas Coelho - Ribeiro, Mariana Letícia (Universidade Federal de São Carlos, 2025)
This study’s objective is to analyze and interpret Alexandra Lucas Coelho’s trilogy of books about Brazil: Vai, Brasil (2015), the novel Deus-dará (2016) and the literature of travel Cinco voltas na Bahia e um beijo para Caetano Veloso (2019). These books evoke concepts that refer to space representation in literature, journalism, questions referring to the colonial past between Portugal and Brazil and identity. Therefore, the objective of this work is to read the trilogy as a project of decolonization of the mind, since the author portraits an image of Brazil and, at the same time, faces her past as being in the ex-colonizer position, which speaks directly to the contemporary Portugal. Furthermore, the work aims to understand how Coelho renews structures, questions facts and resignify identities in her writing.
"Unir pontos num novo desenho": a study on Alexandra Lucas Coelho's portuguese-brazilian trilogy
Keywords: Espaço; Reportagem; Pós-colonial; Identidade; Alexandra Lucas Coelho; Space; Reportage; Postcolonial; Identity; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS